Comparative e-waste plastics biodegradation efficacy of monoculture Pseudomonas aeruginosa strain PE10 and bacterial consortium under in situ condition - Debbarma, Prasenjit; Suyal, Deep Chandra; Kumar, Saurabh; Zaidi, M. G. H.; Goel, Reeta (Frontiers in Microbiology, 2024)
Significant amount of electronics obsoletes or e-waste are being generated globally each year, off these about 20% of which obsolete electronic items constitute the has plastics component. Current remediation practices for e-waste have several setbacks due to its negative impact on environment, agro-ecosystem and human health. Therefore, comparative biodegradation studies of e-waste plastics by monocultures Pseudomonas aeruginosa strain PE10 and bacterial consortium consists of Achromobacter insolitus strain PE2 (MF943156), Acinetobacter nosocomialis strain PE5 (MF943157), P. lalkuanensis PE8 (CP043311), and Stenotrophomonas pavanii strain PE15 (MF943160) under in situ condition was were carried out in situ. Biological treatment of e-waste with these candidates in soil ecosystem have analyzed through diversified analytical techniques such as fourier transform infrared spectroscopy (FTIR), thermogravimetric-derivative thermogravimetry-differential thermal analysis (TG-DTG-DTA) and scanning electron microscopy (SEM). Both Pseudomonas aeruginosa strain PE10 and bacterial consortium have tremendous ability to accelerate the biodegradation process under natural environment. However, FTIR analysis implied that the monoculture had better efficacy than consortium and it was consistent till the incubation period used for the study. Some polymeric bonds such as ν C=C, δ Formatted: Font: Italic Formatted: Font: Italic C-H were completely removed and ν C=C ring stretching, νasym C-O-C, νsym C-H, etc. were introduced by strain PE10. Further, thermal analysis results validated the structural deterioration of e-waste as the treated samples have shown nearly two-fold weight loss (WL) (6.8% WL) than untreated control (3.1% WL) at comparative lower temperature. SEM images provided the details of surface disintegrations. Conclusively, individual monoculture P. aeruginosa strain PE10 could be explored for e-waste bio-recycling in agricultural soil ecosystem thereby reducing the cost, time, and management of bioformulation besides hazardous pollutants reduction.